2018
DOI: 10.1016/j.pnpbp.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A proton MR spectroscopy study of the thalamus in twins with autism spectrum disorder

Abstract: Multiple lines of research have reported thalamic abnormalities in individuals with autism spectrum disorder (ASD) that are associated with social communication impairments (SCI), restricted and repetitive behaviors (RRB), or sensory processing abnormalities (SPA). Thus, the thalamus may represent a common neurobiological structure that is shared across symptom domains in ASD. Same-sex monozygotic (MZ) and dizygotic (DZ) twin pairs with and without ASD underwent cognitive/behavioral evaluation and magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
3
15
1
Order By: Relevance
“…Using a 1.5 Tesla MRI scanner, Batouli et al [38] found NAA (h 2 = 72%), Cho (h 2 = 33%), Cr (h 2 = 51%), and MI (h 2 = 55%) to be heritable in the posterior cingulate cortex. In the MRS study of children with autism, contradictory to the current findings in left thalamus, Cho was not found to be heritable but NAA and MI were found heritable in the thalamus bilaterally [34]. These discrepancies with our findings could possibly be due to differences in age, although this is not currently supported.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Using a 1.5 Tesla MRI scanner, Batouli et al [38] found NAA (h 2 = 72%), Cho (h 2 = 33%), Cr (h 2 = 51%), and MI (h 2 = 55%) to be heritable in the posterior cingulate cortex. In the MRS study of children with autism, contradictory to the current findings in left thalamus, Cho was not found to be heritable but NAA and MI were found heritable in the thalamus bilaterally [34]. These discrepancies with our findings could possibly be due to differences in age, although this is not currently supported.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of common genetic influences on glutamate levels in the thalamus and disease in our study is supported by a report of higher glx levels in the thalamus of subjects at increased familial risk for schizophrenia [33], and a recent study linking higher glx levels to glutamate-related genes associated with risk for schizophrenia [5]. The current heritability estimates are in line with the heritability estimate of glx in the thalamus reported in a twin study in children with autism and controls [34], suggesting a generalizability of the heritability estimate across populations. The present study could not confirm exploratory findings from a MRS study of 2 MZ and 12 DZ twin pairs discordant for schizophrenia describing decreased glutamate levels in the ACC of patients and unaffected co-twins [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, although the overall trend is for lower GABA+ in ASD, it seems that results are inconsistent, owing perhaps to differences in experimental procedures and analysis methods, regions of interest (ROIs), and sample characteristics, as summarized in several recent reviews [Ajram et al, 2019;Ford & Crewther, 2016;SchĂźr et al, 2016]. In the case of Glx, results are even less conclusive, with studies reporting reduced [Bernardi et al, 2011;Corrigan et al, 2013;DeVito et al, 2007;Hegarty et al, 2018;Horder et al, 2013Horder et al, , 2018Kubas et al, 2012;Tebartz Van Elst et al, 2014], equivalent [Ajram et al, 2017;Aoki et al, 2012;Brix et al, 2015;Carvalho Pereira et al, 2018;Endres et al, 2017;Friedman et al, 2006;Goji et al, 2017;Hardan et al, 2008;Horder et al, 2018;Ito et al, 2017;Libero et al, 2016;Mikkelsen et al, 2017;Robertson et al, 2016], or increased [Bejjani et al, 2012;Brown, Singel, Hepburn, & Rojas, 2013;Doyle-Thomas et al, 2014;Page et al, 2006] levels in ASD. In the current study, we sought to extend previous results by measuring GABA+ and Glx simultaneously using current methodology, in a relatively large sample of well-characterized individuals with ASD, including previously unexamined ROIs, and testing the functional relevance of neurometabolite levels by correlating individual differences in MRS measures with behavior and ASD symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the nature and etiology of cerebellar anomalies in ASD require further investigation. A structural meta-analysis has reported modest abnormalities of the thalamus [47], and a study of metabolites in ASD and TD twin pairs reported several significant abnormalities in ASD [374]. Further structural meta-analyses and a cellular study that examined it have not reported thalamic abnormalities [45,48,49].…”
Section: Summary Cautions and Causationmentioning
confidence: 99%